Your craft as a teaching librarian : using acting skills to create a dynamic presence - Sundquist, Jeff; Artman, Julie; Dechow, Douglas R. (Chicago : Association of College and Research Libraries, 2022)
'Library instruction is like acting: There's a live audience, in person or online; you may be doing a one-shot, limited engagement, or play to the same crowd repeatedly over the course of a term; and you usually expect reviews. Most important, instruction is like acting in that you're playing a role, and it's crucial to prepare your performance before you go on in order to shine and connect authentically with students. Your Craft as a Teaching Librarian: Using Acting Skills to Create a Dynamic Presence -a revised and expanded edition of The Craft of Librarian Instruction-captures how acting techniques can sharpen your instructional skills and establish your teaching identity, enliven your performance, and create an invigorating learning experience for your students. It's divided into three entertaining sections: Prepare and Rehearse: Centering yourself, physical and vocal preparation, mindfulness, and avoiding stage fright; Perform and Connect: Role playing, identity, action/reaction, and information literacy; Reflect and Sharpen: and Assessment and adaptation. Chapters feature exercises to explore on your own or with a colleague, question and answer sections to help you identify potential challenges and solutions, and tips on deepening your teaching skills. A glossary of acting terms and a'learn more about it' bibliography provide additional context for the methods and techniques presented. Your Craft as a Teaching Librarian can help you personalize and characterize your teaching presence and help those with little to no teaching experience, instructors dealing with shyness or stage fright, and more experienced librarians in need of a refreshed perspective, adding an undeniable star quality to your instructional performance'--
Bibliography : pages 113-119.
Keywords: Library orientation for college students -- Study and teaching; Information literacy -- Study and teaching (Higher).; Acting -- Technique; Academic librarians -- Training of; Instruction librarians -- Training of .